ASSESSMENT OF THE ORGANIZATION OF PEDESTRIAN TRAFFIC AT THE INTERSECTION OF ROADWAYS [ - Kabenov, О. T.; Ibraev, А. S. (Наука и образование №4, 2020)
The organization of pedestrian traffic is one of the most urgent problems. A large number of road accidents involving pedestrians are caused primarily by conflicts between road users when crossing the roadway. Road accidents involving pedestrians are of great social significance, as they are associated with the death or injury of people. The organization of the movement of pedestrians can be performed on sidewalks along the roadway or when crossing. The latter type of pedestrian traffic is the most dangerous. Crossing the roadway is carried out at pedestrian crossings of various types and different degrees of equipment with technical means of traffic control. Both pedestrians and drivers of vehicles have an impact on the risk of a road accident. But mostly they are caused by pedestrians. The reasons for this is the transition of the roadway to a forbidding traffic light signal or in the wrong place. Also, the reasons are inattentiveness of the pedestrian or driver. It is possible to reduce the probability of a traffic accident involving pedestrians by observing the basic rules, namely: the movement of pedestrians in specially designated areas; the use of retroreflective elements by pedestrians; pedestrians crossing the roadway in accordance with the rules; cross an unregulated intersection under safe conditions.Организация пешеходного движения является одной из актуальнейших проблем. Большое число дорожно-транспортных происшествий с участием пешеходов вызваны первую очередь возникновением конфликтных ситуаций между участниками дорожного движения при пересечении проезжей части. Дорожно-транспортные происшествия с участием пешеходов имеют большое социальное значение, так как связаны с гибелью или травмированием людей. Организации движения пешеходов может осуществляться по тротуарам вдоль проезжей части или при её пересечении. Последний вид пешеходного движения является наиболее аварийным. Пересечение проезжей части осуществляется по пешеходным переходам различного вида и различной степенью оснащения техническими средствами управления дорожного движения. Наиболее опасными являются нерегулируемые пешеходные переходы. Выбор вида пешеходного перехода производится по критерию интенсивности транспортного и пешеходного потоков. Однако на возникновение конфликтных ситуаций, влияет большое число факторов. Для оценки уровня соответствия пешеходного переход условиям движения вводится коэффициент опасности пешеходного перехода равный отношению числа конфликтных ситуаций исходя из условий движения к максимально возможному. При расчете количества конфликтных ситуаций используются мультипликативные степенные модели, где перечень факторов определяется методом априорного ранжирования.
Keywords: научный журнал; отечественное издание; периодическое издание; pedestrian traffic; accident rate; pedestrian crossing; организация пешеходного движения; дорожно-транспортные происшествия; пешеходные потоки; пешеходные переходы